STRATEGIC MANAGEMENT IMPLEMENTATION AND BALANCED SCRECARD ON MANAGEMENT SYSTEM OF MOSQUE - Amin Syukron (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2016)
ABSTRACTIn general, the mosque is only used as a place of worship to pray alone, and some of them were filled with activities by youth mosque and the Amil Zakat department, but not more than 5%. This condition eventually leads to malfunction of the mosque to the maximum, many mosques were deserted condition seemed neglected, and there is even a mosque that just opened at prayer time only. If this condition continues, it is unlikely there will be a gap between the community and the mosque. Not many mosques in which there are Mosques Welfare Board, whose function is to maintain and preserve the mosque. Management strategy (strategic management) is the art and science of formulating, implementing and evaluating cross-functional decisions that enable an organization can achieve its objectives (David, 2006). The management strategy of focusing on the integration of management, marketing, finance, operations, research and development, and computer information systems to achieve organization success. Balanced Scorecard (BSC) is an approach to measure the organization's performance with reference to the four perspectives, namely financial, customer, process internal business, and learning and growth. Key Word: Strategic Management, Balanced Scorecard (BSC), Mosque